Leishmaniasis Beyond East Africa - Jones, Caitlin M.; Welburn, Susan C. (Frontiers in Veterinary Science, 2021)
Climate change is having a substantial impact on our environment and ecosystems and has altered the way humans live, access and utilise resources with increased risk of zoonotic infectious disease encounters. As global temperatures continue to increase, they impact on public health, migration, food security and land conflict, and as new environments become favourable, exposure to disease carrying vectors. Increased forests and natural habitat clearance, for land repurposing, urbanisation, road building and water management are related to an increase in emerging vector borne parasitic diseases. The East African region remains one of the most impacted regions globally for leishmaniasis, a vector borne disease that impacts significantly on the health, wellbeing and livelihoods of affected communities and for which a lack of reporting and control interventions progress towards elimination of this neglected zoonotic disease. As our world continues to transform, both politically and climatically, it is essential that measures are put in place to improve surveillance and disease management with implementation of control measures, including vector control, especially in low- and middle- income countries that are expected to be most impacted by changes in climate. Only through effective management, now, can we be sufficiently resilient to preventing the inevitable spread of vectors into suitable habitat and expansion of the geographical range of leishmaniasis. This review offers a current perspective on Leishmaniasis as an endemic infection in East Africa and examines recent emergence of Leishmania infection in hitherto unaffected regions.